2010
DOI: 10.1095/biolreprod.109.079517
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Functional Pregnancy-Associated Plasma Protein-A (PAPPA) Compromises Mouse Ovarian Steroidogenesis and Female Fertility1

Abstract: The insulin-like growth factor (IGF) system plays an important role in regulating ovarian follicular development and steroidogenesis. IGF binding proteins (IGFBP) mostly inhibit IGF actions, and IGFBP proteolysis is a major mechanism for regulating IGF bioavailability. Pregnancy-associated plasma protein-A (PAPPA) is a secreted metalloprotease responsible for cleavage of IGFBP4 in the ovary. The aim of this study was to investigate whether PAPPA plays a role in regulating ovarian functions and female fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 49 publications
0
53
0
1
Order By: Relevance
“…The gene mediates its action via peptide hormones (like progesterone and growth hormone) and cytokines in target cells and found to be associated with fertilization and embryonic survival rate 27 . Additionally, fibroblast growth factor 2 (FGF2) and progesterone receptor (PGR) were found to be involved in fertilization, development and survival of fertilized embryo [28][29][30] , while growth hormone receptor (GHR), follicle stimulating hormone receptor (FSHR), Leptin (LEP) and pregnancyassociated plasma protein A2 (PAPPA2) were found to be associated with ovulation, calving interval, survival and growth rate of cattle, and perinatal mortality [31][32][33][34][35] . Further, all these proteins, except FGF2, FSHR and PAAPPA2 have direct interaction with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The gene mediates its action via peptide hormones (like progesterone and growth hormone) and cytokines in target cells and found to be associated with fertilization and embryonic survival rate 27 . Additionally, fibroblast growth factor 2 (FGF2) and progesterone receptor (PGR) were found to be involved in fertilization, development and survival of fertilized embryo [28][29][30] , while growth hormone receptor (GHR), follicle stimulating hormone receptor (FSHR), Leptin (LEP) and pregnancyassociated plasma protein A2 (PAPPA2) were found to be associated with ovulation, calving interval, survival and growth rate of cattle, and perinatal mortality [31][32][33][34][35] . Further, all these proteins, except FGF2, FSHR and PAAPPA2 have direct interaction with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Lhcgr encodes the LH receptor that is required for ovulation, cumulus cell expansion, and the resumption of meiosis (67); Cyp11a1 encodes cytochrome P450 side chain cleavage, the rate-limiting enzyme for progesterone biosynthesis (18,68); the EGFR contributes to LH-stimulated expansion of cumulus granulosa cells, resumption of meiosis, and ovulation (27,69,70); Cyp19a1 encodes aromatase, the rate-limiting enzyme in estrogen biosynthesis (71); Inha encodes for the inhibin hormone subunit inhibin-␣ that inhibits FSH expression by the anterior pituitary (72); Hsd17b1 encodes the enzyme that converts androstenedione and estrone to testosterone and estradiol-17␤, respectively, and is required for normal ovulation and corpus luteum formation (73); and Pappa encodes a secreted metalloproteinase that cleaves IGF-binding proteins and contributes to estrogen and progesterone biosynthesis and to ovulation (74).…”
Section: Discussionmentioning
confidence: 99%
“…by the co-treatment of hCG with 10 −8 M or greater concentration of zearalenone or ␣-zearalenol. Nyegaard et al [53] reported that Pregnancy-Associated Plasma Protein-A (PAPPA), a chemical could cause the reduction of progesterone content, could significantly reduce the P450-17˛1 and 17ˇ-HSD mRNA levels induced by hCG stimuli in mouse ovarian. Thus, the ability to affect hCG inducible steroidogenesis provided a unique functional feature for screening environmental endocrine disruption that may occur during exposure.…”
Section: Discussionmentioning
confidence: 99%